Reformulation of Calvinist Ethics from a Study Turats Perspective - Zahro, Fatimatuz; Irama, Yoga (Proceedings of International Conference on Muslim Society and Thought, 2024)
Abstract: Western culture that is full of discipline, hard work, and unyielding according to Max Weber is the implication of the application of Calvinism ethics resulting from Protestant teachings. This phenomenon does not seem to have received serious application and attention from Muslims even though Islam itself is a religion that is full of teachings of hard work and perseverance. In the Islamic world, there is what is called Islamic Calvinism. Indeed, further, careful and scientific efforts are needed so that there is no misperception about the Calvinism desired by Islam and the Calvinism originating from Protestantism. This is what will be discussed in this article, through the literature study method, researchers will examine how far the ethics of Islamic Calvinism are understood as one of the sources of community progress through the search for classical books (turats).